Echo made easy - Kaddoura, Sam (Churchill Livingstone, 2002)
This book aims to provide a practical and clinically useful introduction to echo - much of which is easy - for those who will be using, requesting and possibly interpreting it in the future. The book is aimed particularly at doctors in training and medical students. It is also hoped that it may be of interest to other groups - established physicians and general practitioners, cardiac technicians, nurses and paramedics. It aims to explain the echo techniques available, what an echo can and cannot give, and - importantly - put echo into a clinical perspective. It is by no means intended as a complete textbook of echo and some aspects are far beyond its scope (eg, complex congenital heart disease and pediatric echo).
Keywords: echokardiografie; ECHOKARDIOGRAFIE DOPPLEROVA; radiologie, nukleární medicína a zobrazovací metody; kardiologie; Echocardiography